Phytochemical profile, antioxidant, antidiabetic, and antimicrobial activities of Parkia timoriana bark extracts - ATMIRA SARIWATI; VENTY SURYANTI; FITA SARI; ICHIRO KAMEI; ELYNA WAHYU TRISNAWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sariwati A, Suryanti V, Sari F, Kamei I, Trisnawati EW. 2024. Phytochemical profile, antioxidant, antidiabetic, and antimicrobial activities of Parkia timoriana bark extracts. Biodiversitas 25: 2427-2433. Plants have various bioactive compounds that have pharmacological activity. Kedawung (Parkia timoriana (DC) Merr) is an indigenous plant in Indonesia that contains bioactive compounds. The leaves, bark, seeds, and roots of P. timoriana are commonly used in traditional medicine. The purpose of this study was to determine the chemical composition of P. timoriana bark extract and to assess its antioxidant, antidiabetic, and antibacterial activity. The bark of P. timoriana was extracted with various solvents that differ in polarity, such as water, methanol, ethyl acetate, and hexane. All extracts were investigated for antioxidant activities by 2,2-diphenyl-1-picrylhydrazyl) (DPPH) free-radical and 2,2’-azinobis (3-ethylbenz-thiazoline-6-sulfonic-acid) (ABTS) scavenging ability. The in-vitro antidiabetic activity was carried out by ?-amylase and ?-glucosidase inhibition. Antibacterial and antifungal activities were determined by the agar disc diffusion method. Parkia timoriana bark extracts contained alkaloids, flavonoids, steroids, tannins, terpenoids, saponins, reducing sugars, and cardiac glycosides. The ethyl acetate extract possessed the highest total phenolics, alkaloids, flavonoids, saponins, tannic acid, and terpenoids. Secondary metabolites in all extracts contributed to free radical scavenging, antidiabetic, antibacterial, and antifungal properties. The P. timoriana bark contains natural chemical compounds that might be useful as therapeutic agents for producing bioactive products and pharmaceuticals in the future.